The relationship between genetic variants associated with primary ovarian insufficiency and lipid profile in women recruited from MASHAD cohort study - Mohammad Reza Mirinezhad; Hamideh Ghazizadeh; Maliheh Aghsizadeh; Mohammad Zamiri Bidary; Alireza Naghipour; Elahe Hasanzadeh; Mahdiyeh Yaghooti-Khorasani; Ali Ebrahimi Dabagh; Mohammad Reza Shadmand Foumani Moghadam; Nazanin Sheikh Andalibi; Zeynab Naseri Far; Habibollah Esmaily; et al. (BMC, 2022)
Abstract Background and aim Primary Ovarian Insufficiency (POI) is defined by the occurrence of menopause before the age of 40 years. It is often associated with cardiovascular disease (CVD). The purpose of this study was to explore the relationship between POI-associated genotypes cardiometabolic disorder risk factors. Methods One hundred seventeen women with POI and one hundred eighty-three healthy women without POI were recruited in this study. DNA was extracted and analyzed using ASO-PCR or Tetra ARMS-PCR. Lipid profiles were also assessed. Results Multivariate logistic regression analysis showed that individuals with GG vs. TT genotype of the rs1046089 SNP were more likely to have a higher serum LDL (p = 0.03) compared to the control group. There was also a significant association between low serum HDL and rs2303369 and rs4806660 SNP genotypes in the POI group. In the POI group, the percentage of those with high total cholesterol was lower in those with a CC genotype compared to those with a TT genotype (p = 0.03). Conclusion Some SNPs reported to be associated with POI appear to be independently associated with dyslipidemia. These results may be helpful to identify subjects with POI who may be susceptible to CVD.